Climate variability and aridity modulate the role of leaf shelters for arthropods: A global experiment. (21st March 2022) - Romero, Gustavo Q.; Gonçalves‐Souza, Thiago; Roslin, Tomas; Marquis, Robert J.; Marino, Nicholas A.C.; Novotny, Vojtech; Cornelissen, Tatiana; Orivel, Jerome; Sui, Shen; Aires, Gustavo; Antoniazzi, Reuber; Dáttilo, Wesley; et al.
Abstract: Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to aridity, high temperatures, and climate variability might find shelter in microclimatic refuges, such as leaf rolls built by arthropods. To explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation, and climate, we conducted a distributed experiment comparing arthropods in leaf rolls versus control leaves across 52 sites along an 11, 790 km latitudinal gradient. We then probed the impact of short‐ versus long‐term climatic impacts on roll use, by comparing the relative impact of conditions during the experiment versus average, baseline conditions at the site. Leaf shelters supported larger organisms and higher arthropod biomass and species diversity than non‐rolled control leaves. However, the magnitude of the leaf rolls' effect differed between long‐ and short‐term climate conditions, metrics (species richness, biomass, and body size), and trophic groups (predators vs. herbivores). The effect of leaf rolls on predator richness was influenced only by baseline climate, increasing in magnitude in regions experiencing increased long‐term aridity, regardless of latitude, elevation, and weather during the experiment. This suggests that shelter use by predators may be innate, and thus, driven by natural selection. In contrast, the effect of leaf rolls on predator biomass and predator body size decreased with increasing temperature, and increased with increasing precipitation, respectively, during the experiment. The magnitude of shelter usage by herbivores increased with the abundance of predators and decreased with increasing temperature during the experiment. Taken together, these results highlight that leaf roll use may have both proximal and ultimate causes. Projected increases in climate variability and aridity are, therefore, likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence. Abstract : Species sensitive to harsh climatic conditions often find shelter in microclimatic refuges, such as leaf rolls built by arthropods. Both long‐term climate and weather conditions during our global experiment significantly influenced arthropod occupancy of leaf rolls. Leaf shelters support larger organisms and higher species richness than non‐rolled control leaves, and these effects were strengthened under arid conditions. Evidence suggests that shelter use behavior by predators may be innate, and thus, driven by natural selection. Projected increases in climate variability and aridity are therefore likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence.